A Spatially Explicit, Empirical Estimate of Tree‐Based Biological Nitrogen Fixation in Forests of the United States. Issue 2 (20th February 2020) - Staccone, Anika; Liao, Wenying; Perakis, Steven; Compton, Jana; Clark, Christopher M.; Menge, Duncan
Abstract: Quantifying human impacts on the nitrogen (N) cycle and investigating natural ecosystem N cycling depend on the magnitude of inputs from natural biological nitrogen fixation (BNF). Here, we present two bottom‐up approaches to quantify tree‐based symbiotic BNF based on forest inventory data across the coterminous United States and SE Alaska. For all major N‐fixing tree genera, we quantify BNF inputs using (1) ecosystem N accretion rates (kg N ha −1 yr −1 ) scaled with spatial data on tree abundance and (2) percent of N derived from fixation (%Ndfa ) scaled with tree N demand (from tree growth rates and stoichiometry). We estimate that trees fix 0.30–0.88 Tg N yr −1 across the study area (1.4–3.4 kg N ha −1 yr −1 ). Tree‐based N fixation displays distinct spatial variation that is dominated by two genera, Robinia (64% of tree‐associated BNF) and Alnus (24%). The third most important genus, Prosopis, accounted for 5%. Compared to published estimates of other N fluxes, tree‐associated BNF accounted for 0.59 Tg N yr −1, similar to asymbiotic (0.37 Tg N yr −1 ) and understory symbiotic BNF (0.48 Tg N yr −1 ), while N deposition contributed 1.68 Tg N yr −1 and rock weathering 0.37 Tg N yr −1 . Overall, our results reveal previously uncharacterized spatial patterns in tree BNF that can inform large‐scale N assessments and serve as a model for improving tree‐based BNF estimates worldwide. This updated, lower BNF estimate indicates a greater ratio of anthropogenic to natural N inputs, suggesting an even greater human impact on the N cycle. Key Points: N‐fixing trees in the temperate United States contribute less reactive N than previously thought Alnus and Robinia fix the majority of tree‐based N fixation in the United States The flux of fixed N from trees is similar to that from understory plants or asymbiotic fixers across the United States